Hubungan Karakteristik Penderita Hipertensi dengan Tingkat Kepatuhan Minum Obat di RSUD Embung Fatimah Kota Batam - Suci Fitriani Sammulia; Aprilya Sri Rachmayanti; Erna Chintia (Yayasan Literasi Sains Indonesia, 2022)
Hypertension is one of the non-communicable diseases which is a problem in the health sector and is often found in primary health services. A person is said to suffer from hypertension when systolic blood pressure ≥ 140 mmHg and diastolic pressure ≥ 90 mmHg. The use of antihypertensive drugs alone is proven to be insufficient to produce long-term blood pressure control effects if it is not supported by adherence to the use of antihypertension. The high incidence of hypertension in the world, is influenced by two types of factors, namely factors that cannot be changed such as age, sex, and race. Furthermore, factors that can be changed include obesity, alcohol consumption, lack of exercise, excessive salt consumption, and smoking habits. The purpose of this study was to determine the relationship between the characteristics of hypertension sufferers with the level of adherence to take medication at Embung Fatimah District Hospital in Batam. This study used a cross-sectional descriptive study method using the MMAS-8 (Morisky Medication Adherence Scale) questionnaire. Respondents who were the subject of this study were suffering from hypertension at Embung Fatimah Regional Hospital in Batam. The sampling technique used is a simple random sampling technique with a total sample of 96 people. The results of this study generally showed that 36.5% of patients had high adherence to take hypertension medication while the remaining 13.5% of patients had moderate adherence and as many as 50% had high adherence. To support the success rate of hypertension treatment can be done with the presence of hypertension counseling so that adherence to taking medication for hypertension sufferers can increase.